An assessment of knowledge use and knowledge management maturity among the micro, small and meduim enterprise sector in Zambia - Sikazwe, Dennis (Library and Information Studies Centre (LISC), 2015)
The focus of this study was to establish the knowledge use and Knowledge Management (KM) maturity among the Micro, Small and Medium Enterprise (MSME) Sector in Zambia. This is a domain that has received little attention in the Zambian business and economics literature, partially because of the newness of KM as a business concept. Knowledge Management is a very important aspect as far as innovation and competitiveness are concerned in the knowledge economy. Since the inception of the open market economy in Zambia in 1992 and the move to diversify Zambia's national economy from state control into private hands, the MSMEs still seem to be struggling with lack of innovation and competitiveness. Despite several attempts to boost the sector's viability, little success has been recorded.